Petrology of granulites of the Shillong Plateau from west Garo Hills district, Meghalaya, India - Bhagabaty, B; Mazumdar, AC (Journal of Nepal Geological Society, 2008)
Intercalated and cofolded bands of Mg-poor and Mgrich Cordierite + Sillimanite + Garnet + Orthopyroxene bearing metapelites and Orthopyroxene + Clinopyroxene ± Hornblende bearing basic granulites constitute locally the garnuite facies terrain in the West Garo Hills district in Meghalaya, India. These rocks show the evidences of poly metamorphism indicating the peak events, the pre-S2 granulite facies metamorphism (M2) which was followed by subsequent M3, syn-S2, the dominant solid-state fabric-forming episode in the area. The last metamorphic phase is M4 events postdated S2. The earliest metamorphic fabrics so far recognized are as inclusion phases (M1, syn- to post-S1) in M2 porphyroblasts representing another high-grade metamorphic events, which erased out due to the subsequent metamorphic episodes. Petrographic evidences indicate that metapelites preserve prograde P-T path and high temperature anatexis of the rocks before attaining granulite facies condition (M2) while textural features in basic granulites clearly indicate a prograde path in terms of hornblende breakdown reaction. The geothermobarometric data on core composition pre- S2 (M2) mineral assemblages in combination with a comparison of relevant experimental data indicate that the peak metamorphic average temperature 730ºC and 750°C in metapelites and basic granulites, respectively and pressure around 5.3 – 5.9 kbar. This P-T estimates of the present study is relatively lower than the ‘true peak’ P-T condition of pre- S2, (M2), assemblages, which may have been modified by chemical reequilibration during subsequent M3 and M4 stages. The retrograde P-T history is well documented in the rocks of the area. The retrograde P-T path as revealed by the mineral assemblages forming corona on granulite facies minerals (Garnet corona on Pyroxene + Plagioclase in basic granulites) or restabilisation of Fe +Mn- rich Garnet on preexisting Garnet or post- S2 fabric defined by Sillimanite + Biotite + Quartz in metapelites. The thermobarometric studies on coronitic Garnet in basic granulites quantify an isobaric cooling (IBC) through 140°C during M4 stage with minimal decrease in pressure about 0.5 kbar; while metapelites indicate the IBC- path by a decrease of temperature of ~180°C for a decrease of 1.0 kbar. Thus, the present study indicates an anticlockwise P-T path followed by M1- M2 prograde path and retrograde M3 and M4 as reflected from thermobarometric results and critical textures and thereby implying that the granulite facies netamorphism was caused due to magmatic underplating beneath the continental crust. Journal of Nepal Geological Society, 2007, Vol. 36 (Sp. Issue) p.7